To Study the Social Influence of Vocational Education on Socio-Economic Growth: The Impact of Vocational Education on Socio-Economic Development (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The goal of Vocational Education (VE) to train students in the essential manipulation skills, safety judgments, and relevant knowledge in order to place them in the suitable employment. Mathematical, communication, information processing, and decision-making abilities, as well as interpersonal skills, are taught to students in this programme. Students who gain these abilities will be more equipped to handle the demands of the workplace, which in turn will lead to greater job satisfaction. A person's professional and functional abilities can be improved by vocational education. This ever-changing world, with its many facets, need ongoing education to stay on top of one's game. Skill-based education, a necessity for the economy, is absent in existing educational programmes.